Evaluation of in vitro Cholesterol esterase inhibitory and in vivo Anti-hyperlipidemic activity of aqueous extract of Plukenetia conophora Mull. Arg. (Euphorbiaceae) - Glory Oluremilekun Ajayi; Aleshe Modupe Nofisat; Bassey Mfon Jessica (International Journal of Phytomedicine, 2019)
Hyperlipidemia is a condition of abnormally high lipids levels in the blood which has been ranked as one of the greatest risk factors contributing to prevalence and severity of coronary heart disease. The available antihyperlipidemic drugs have been associated with some side effects however, herbal management of hyperlipidemia are relatively safe, cheap and readily available. P. conophora is an edible plant consumed in Nigeria as snack and speculated to have beneficial effect on blood lipid profile. The present study evaluates anti-hyperlipidemic effect of aqueous extract of cooked P. conophora nut using in vivo and in vitro experimental models. The anti-hyperlipidemic activity was evaluated using tyloxapol induced-hyperlipidemic rats by intraperitoneal injections of Tyloxapol at a dose of 300 mg/kg body weight and high cholesterol-diet induced rats by oral administration of high cholesterol diet for 60 days. Cholesterol esterase enzyme inhibition was used for the in vitro evaluation. Aqueous extract of P. conophora at varying doses, reduced the elevated lipid parameters in both models; the dose of 500 mg/kg showed comparable hypolipidemic effects with standard drug (Simvastatin) at 10 mg/kg (P<0.01). The extract also inhibited cholesterol esterase enzyme with IC50 value of 129.30±0.10μg/ml while Simvastatin with IC50 value of 51.42±0.13μg/ml. Preliminary phytochemical analysis revealed the presence of; Flavonoids, saponin, cardiac glycoside, alkaloids, tannins, steroids and reducing sugar. P. conophora extract exhibited strong hypolipidemic activity and the dose of 500mg/kg demonstrated equipotent activity as the standard drug; Simvastatin 10mg/kg. The extract also showed inhibitory activity against pancreatic cholesterol esterase enzyme; hence can be used to limit absorption of dietary cholesterol, prevent and treat hyperlipidemia.